Production Functions for Irrigation Water and Nitrogen Requirements of Early Cauliflower Grown in Greenhouse - Singla, Chetan; Singh, K G (Journal of Agricultural Engineering, 2009)
A field study on fertigation of cauliflower (Brassica Oleracea var. botrys Linn.) using drip irrigation system was undertaken with three rates of nitrogen application (100%, 75% and 50%) of recommended dose applied in three splrts (50 % of dose at planting time, 25% at 30 days after planting and 25% at 60 days after planting) and three levels of irrigation at IW/CPE ratio of 0.5, 0.75 and 1.0 in fan pad cooled greenhouse and naturally ventilated greenhouse respectively. Various prediction models viz. linear, quadratic, square root and three halves governing the relationship between irrigation water, nitrogen fertilizer and the yield of drip irrigated off-season cauliflower were developed. The studies revealed that the maximum yield of 1.2 t/ha and 1.05 t/ha of early cauliflower could be obtained under irrigation schedule based on IW/CPE=0.5 and 100% of recommended nitrogen dose in both the greenhouses. Square root model was the best prediction model for assessing the impact of irrigation water and nitrogen dose on crop yield, with RÂ² value (0.956) in fan pad cooled greenhouse (RMSE=4.18) and quadratic model with RÂ² value (0.901) in naturally ventilated greenhouse (RMSE=5.72). The prediction model mdicated that cauliflower showed a declining response to the amount of irrigation water having negative regression coefficient. The crop response was positive to nitrogen application in its square root terms indicating its favourable influence on crop yield at higher doses.